MicroRNAs in opioid addiction: elucidating evolution - Wood, Emily J.; Lipovich, Leonard (Frontiers in Genetics, 2012)
Three reviews in the Frontiers Research Topic “Non-Coding RNA and Addiction” (Zheng et al 2012; He and Wang 2012; Rodriguez 2012 in press), grouped under the chapter “MicroRNAs and Morphine,” focus on the contribution of microRNAs to opioid abuse. Although animal models have been fundamental to our understanding of addiction pathways, the assumption that microRNAs implicated in opioid tolerance – and their binding sites in mRNAs – are conserved in mammalian evolution was not examined by the authors. Inspired by recent reports which highlight a surprising lack of evolutionary conservation in noncoding-RNA genes, in this perspective we use public genome, annotation, and transcriptome datasets to verify microRNA host gene, mature microRNA, and microRNA binding site conservation at key loci functional in opioid addiction. We reveal a complex evolutionary landscape in which certain directional regulatory edges of the microRNA-mRNA hub-and-spoke network lack pan-mammalian conservation.